KEBERADAAN LEMBAGA PENDIDIKAN ANAK USIA DINI (PAUD) BAGI KELUARGA MISKIN PERKOTAAN(STUDI PAUD MUTIARA BUNDA KECAMATAN PEKANBARU KOTA) - Azmi, Mutia Olia; ", Basri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study titled Existence Institute of Early Childhood Education (ECD) For poorfamilies in the city of Pekanbaru (ECD studies Mother of Pearl District of Pekanbaru City).Researchers interested in this theme because in Pekanbaru City Early Childhood Education(ECD) is growing. In early childhood education is synonymous with expensive andmiddleclass family owned, but now children - children from poor families also attended aneducation at an early age through the Institute of Early Childhood Education (ECD). Withthe formulation of the problem factors - factors that encourage parents put their children inearly childhood institutions, and How to view (perception) of parents of the existence of earlychildhood institutions.The theory used in this study is the Theory of Education, Theory of the Family, Theoryof view (Perception), Theory of the Poor, Structural and Functional Theory. The researchmethod used is descriptive qualitative. The respondents were 10 people, 2 men - men and 8women, in which respondents were selected based on criteria that parents who came frommiddle-class economy.The results showedthat the factors – factors of parents who are in an environment ofpoor families put their childrenat the Institute for Early Childhood Education (ECD) Motherof Pearlis afactor of importance of education, educational cost factor, the factor of socialrelationships, and infrastructure factors. View (perception) parents are institutions (ECD) isimportant forchildren – children at an early age, as well as givinga lot of progress andnegative child development lies in the child quickly performimitation (impersonation).Teacher steaching professional and social relationships already established throughmeetings, recreation with teachers and parents as well asin the event ofa disaster.Keywords: Education, Early childhood, Poor